Effects of Osseointegration by Bone Morphogenetic Protein-2 on Titanium Implants In Vitro and In Vivo - Fu-Yuan Teng; Wen-Cheng Chen; Yin-Lai Wang; Chun-Cheng Hung; Chun-Chieh Tseng (Bioinorganic Chemistry and Applications)
This study designed a biomimetic implant for reducing healing time and achieving early osseointegration to create an active surface. Bone morphogenetic protein-2 (BMP-2) is a strong regulator protein in osteogenic pathways. Due to hardly maintaining BMP-2 biological function and specificity, BMP-2 efficient delivery on implant surfaces is the main challenge for the clinic application. In this study, a novel method for synthesizing functionalized silane film for superior modification with BMP-2 on titanium surfaces is proposed. Three groups were compared with and without BMP-2 on modified titanium surfaces in vitro and in vivo: mechanical grinding; electrochemical modification through potentiostatic anodization (ECH); and sandblasting, alkali heating, and etching (SMART). Cell tests indicated that the ECH and SMART groups with BMP-2 markedly promoted D1 cell activity and differentiation compared with the groups without BMP-2. Moreover, the SMART group with a BMP-2 surface markedly promoted early alkaline phosphatase expression in the D1 cells compared with the other surface groups. Compared with these groups in vivo, SMART silaning with BMP-2 showed superior bone quality and created contact areas between implant and surrounding bones. The SMART group with BMP-2 could promote cell mineralization in vitro and osseointegration in vivo, indicating potential clinical use.